Flow in the anterior chamber of the eye with an implanted iris-fixated artificial lens. (7th August 2017) - Tweedy, Jennifer H; Pralits, Jan O; Repetto, Rodolfo; Soleri, Paolo
Abstract: Flow in the aqueous humour that fills the anterior chamber of the eye occurs in response to the production and drainage of the aqueous humour, and also due to buoyancy effects produced by thermal gradients. Phakic intraocular lenses are manufactured lenses that are surgically inserted in the eyes of patients to correct refractive errors. Their presence has a dramatic effect on the circulation of the aqueous humour, resulting a very different flow in the anterior chamber, the effects of which have not been extensively investigated. In this article we use a simplified mathematical model to analyse the flow, in order to assess the effect of the implanted lens on the pressure drop required to drive the flow and also on the wall shear stress experienced by the corneal endothelial cells and the cells of the iris. A high pressure drop could result in an increased risk of glaucoma, whilst raised shear stress on the cornea could result in a reduction in the density of endothelial cells there, and on the iris it could result in the detachment of pigment cells, which block the outflow of the eye, also leading to glaucoma. Our results confirm those of previous fully numerical studies, and show that, although the presence of the lens causes significant differences in the flow topology and direction, the typical magnitudes of the shear stress are not significantly changed from the natural case. Our semi-analytical solution allows us to perform a thorough study of the dependence of the results on the controlling parameters and also to understand the basic physical mechanisms underlying flow characteristics.